Pemeriksaan SADARI dan SADASI Internal Bhayangkari Polres Pelabuhan Makassar - Purbanova, Reni; Asmi, A. Syamsinar; Wahyuni, Ria; Putri, Lusia Eka; Pannyiwi, Rahmat (Asosiasi Guru dan Dosen Seluruh Indonesia, 2023)
Breast self-examination (SADARI) is the development of a woman's awareness of the condition of her own breasts. This action comes with specific steps to detect breast cancer early. This activity is very simple and can be done by all women without the need to feel embarrassed to the examiner, does not require cost, and for busy women only need to provide time for approximately five minutes. Its sensitivity rate (its ability to detect breast cancer) is around 20-30%. The purpose of this PkM is to socialize and train women on how to detect breast cancer early with breast cancer self-detection techniques (SADARI). The special target of this PkM activity is to provide assistance by training PKK Bhayangkari women of Makassar Port, South Sulawesi. The method of this service activity is carried out by providing assistance to the examination of PKK Bhayangkari women of Makassar Port, South Sulawesi, who can perform SADARI properly and correctly. Based on the results, a significant thing was obtained, namely that the cadre mothers understood the dangers of breast cancer, and performed SADARI correctly.